The influence of Involvement and participation, compensation, communication and work-life balance on Employee Engagement: A Case of Insurance Companies in Batticaloa District - Thavakumar, D.; Evangeline, S.J. (Faculty of Graduate Studies , University of Sri Jayewardenepura, 2016)
Employee engagement is a fulfilling work-related state of mind characterized by feelings of energy, dedication, and more concentration towards role performance. This concept is rapidly gaining popularity and is used in workplace to retain quality employees. This study examines the factors that influence employee engagement and measures the overall level of employee engagement in insurance sector. Four main factors were identified such as involvement and participation; compensation; communication and work-life balance. To attain the objectives, the quantitative method was used and data were collected through questionnaires. A total of 210 questionnaires were distributed to the employees who are in marketing and distribution level in insurance companies in Batticaloa District. Only 202 questionnaires were received and used for further analysis. The data were analyzed using Pearson correlation and multiple regression analysis. The findings exhibited that, there were relationship between factors and employee engagement and also employee engagement of employees is in high level in insurance companies in Batticaloa District. However, all factors are positively and significantly correlated with employee engagement. Lastly, the regression analysis between factors and employee engagement indicated that only 48% of total variance of employee engagement was explained by factors of employee engagement. In conclusion, it is observed that involvement and participation, compensations and communication have influence on the employee engagement. This shows that employers need to develop a proper and well-structured engagement policies and practices in attaining high level of engagement among the employees.
Keywords: Employee Engagement, Involvement and Participation, Compensation, Communication and Work-life Balance